(untitled) (TERRA LATINOAMERICANA, 2026)
The application of biopolymers in wastewater treatment processes represents an ef fective strategy for mitigating the environmental impact of agricultural and domestic discharges. The objective of this research was to analyse the ef fectiveness of biopolymers for wastewater treatment in the area of influence of the Tragadero Lagoon, in the province of Jauja, Junín, Peru. Physicochemical parameters such as pH, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), faecal coliforms, and chromium were evaluated. Using the coagulation–flocculation method, doses of 1.2 mL of pectin and 1.2 g of chitosan were administered to 500 mL of wastewater, with mechanical agitation at 120 rpm for three hours, followed by one hour of sedimentation. An experimental design wasadopted to interpret the physicochemical data of the ef fluent before and af ter the application of the biopolymers. Results: The initial physicochemical analysis of wastewater from the Tragadero Lagoon showed pH 7.30, BOD 146.6 mg L–1, COD 75.0 mg L–1, TSS 51.0 mg L–1, faecal coliforms 1.3 × 10³ NMP/100 mL, and chromium 0.147 mg L–1, whereas the second physicochemical analysis showed pH 7.50, BOD 78.0 mg L–1, COD 48.5 mg L–1, TSS 42.0 mg L–1, faecal coliforms 2.4 × 10² NMP/100 mL, and chromium < 0.001 mg L–1. The use of biopolymers for wastewater treatment in the area surrounding the Tragadero Lagoon could be an ef fective solution for reducing pollution and preserving its ecosystem, since biopolymers have advantages over other wastewater treatment methods, such as their ef fectiveness in removing contaminants, their biodegradable nature, and their low cost. The information obtained in this study will be useful for environmental entities, authorities, and the local population in implementing sustainable wastewater treatment strategies.